Soziale Bewegungen und Gewerkschaften im Wechselspiel - Pernicka, Susanne (Forschungsjournal Soziale Bewegungen, 2019)
Vereinzelte Verweise auf westmitteleuropäische Länder, die USA oder Australien machen aber deutlich, dass die neoliberale Politik auch in diesen Ländern zu einer Verschärfung der Spaltungen zwischen verschiedenen Gruppen auf dem Arbeitsmarkt und zwischen diesen und den "Abgehängten" ohne Aussicht auf eine dauerhafte Integration in den Arbeitsmarkt geführt hat. Die Fragen nach der Nachhaltigkeit von Allianzen zwischen Gewerkschaften und sozialen Bewegungen, den politischen und gesellschaftlichen Orientierungen (kosmopolitische Öffnung versus nationalistische und gruppenspezifische Schließungen) sowie deren Effekten bleiben aber letztlich offen und können durch den Verweis auf Polanyis "Pendel" zwischen ökonomischer Liberalisierung und protektionistischer Gegenbewegung kaum zufriedenstellend beantwortet werden. Wie die Herausgeber des Sammelbandes in den Schlussfolgerungen betonen, handelt es sich bei der aktuellen Phase des Neoliberalismus um eine seit mehreren Dekaden andauernde Bewegung von oben, die ungeachtet der Finanz- und Eurokrise(n) ihre hegemoniale Stellung kaum eingebüßt und bestehende Spaltungen und Konflikte zwischen und innerhalb von Gewerkschaften, sozialen Bewegungen und Parteien stark vergrößert hat.
Keywords: Polanyi's pendulum; pendulum; social movements

Polanyi in Zeiten des Populismus - Bärnthaler, Richard (Wirtschaft und Gesellschaft, 2019)
Keywords: HOLMES, Christopher; POLANYI, Karl, 1886-1964; Polanyi in Times of Populism: Vision & Contradiction in the History of Economic Ideas (Book); book review; nonfiction

Karl Polanyi: Ein Denker für die heutige Zeit - Thomasberger, Claus (Wirtschaft und Gesellschaft, 2019)
Keywords: DALE, Gareth; Karl Polanyi: A Life on the Left (Book); POLANYI, Karl, 1886-1964; book review; nonfiction

Polanyi neu entdecken: Freiheit, Demokratie und Sozialismus - Novy, Andreas (Rediscover Polanyi: Freedom, democracy and socialism., 2018)
Keywords: BRIE, Michael; Karl Polanyi's Vision of a Socialist Transformation (Book); NONFICTION; Polanyi neu entdecken: Das hellblaue Bandchen zu einem moglichen Dialog von Nancy Fraser und Karl Polanyi (Book); THOMASBERGER, Claus; book review; fiction; nonfiction

A Missed Opportunity - Kesting, Stefan; Hughes, Peter (Erwägen Wissen Ethik, 2014)
The authors respond to arguments raised by political scientist Hartmut Elsenhans in his article "Capitalism and Global History: Some Thoughts on History and Theory," published within the issue. Topics discussed include the double movement theory of political economist Karl Polanyi, social factors that influence capitalism, and the way Elsenhans interpreted modern capitalism using Marxian materialism concepts.
Keywords: ELSENHANS, Hartmut; capitalism; history; materialism

Ideen und Interessen. Zum Verhältnis von Religion und wirtschaftlicher Entwicklung - Deutschmann, Christoph (Ideas and interests. On religion and economic development, 2013)
While concentrating on the rise of modern capitalism, Weber’s seminal studies have little to say about the impact of religions on contemporary economic development. The paper comments about recent approaches to find an answer to the questions Weber left open. If one disregards a priori constructions of culturalist and rational-choice-theories, these approaches end up again in restating the circular relationship between ideas and interests showed already by Weber, albeit clearly with a higher emphasis on interests. However, the author argues that it would be premature to interpret this result simply as a confirmation of Weber’s “disenchantment” thesis. Rather, it goes back to the transformation of the economy itself into an entity that preaches “values”, proclaims “visions” and in this sense develops an affinity to religious movements. The author deepens this view by referring to Marx’ and Polanyi’s interpretation of capitalism as a system of disembedded markets. The disembedding of markets gives rise to a historically new potential of social uncertainty which the actors need to cope with, thereby developing symbolisms showing striking affinities with religious forms. Nevertheless, the analogies between capitalism and religion are limited. (English)
Keywords: Entgrenzung; Institutionen; Kontingenz; Märkte; Säkularisierung; WEBER, Max, 1864-1920; Werte; capitalism; capitalism - religious aspects; consumption (economics); contingency; disembedding; economic aspects; economic development; institutions; markets; philosophy; religion; religion and sociology; religious aspects; secularization; values

Wealth and Poverty in Postindustrial Societies. The Pragmatistic Approach to Their Empirical Assessment - Kreutz, Henrik (Angewandte Sozialforschung, 2007)
On the terms of Karl Polányi's concept of the "Commodity Fiction" a theoretical conception of poverty is developed, which defines "absolute poverty" as a process, the terminal state of which is "annihilation". Within this process of "totalitarian consumption" consumer goods do not serve human needs in the first line but turn more and more into "consuming goods" which destroy the independence of human actors step by step and finally transform them into "cyborgs", i.e. creatures, whose lives and intentions become fictions of this system of totalitarian consumption.
Keywords: absolute poverty; commodity fiction; consumer goods; consumerism; consumption (economics); fictitious commodities; income distribution; postindustrial societies; poverty; wealth

Wirtschaftsethik der ›always embedded market economy‹. Überlegungen zu einer Idee von Polanyi - Haase, Michaela (Zeitschrift für Wirtschafts- und Unternehmensethik, 2021)
Capitalism is a social relation that cannot be reduced to the characteristics associated with it - markets, private property, profit and profit orientation. This relation can be shaped in different ways. The article refers to Karl Polanyi’s idea of the ›always embedded market economy‹ in order to develop basic characteristics of an example of post-capitalist economic ethics. Alternate abstract: Der Kapitalismus ist ein soziales Verhältnis, das sich nicht auf die mit ihm in Verbindung gebrachten Merkmale - Märkte, Privateigentum, Gewinn- und Profitorientierung - reduzieren lässt. Dieses Verhältnis kann auf verschiedene Weise ausgestaltet werden. Der Beitrag referiert auf die Idee der ›always embedded market economy‹ von Karl Polanyi, um Grundzüge einer postkapitalistischen Wirtschaftsethik zu entwickeln.
Keywords: business and economics; capitalism; ethics; market economies; philosophy; private property

Permanenter Notstand und der Kampf um gute Sorge(arbeit) – Polanyi’sche Doppelbewegungen in der Marktgesellschaft - Décieux, Fabienne; Becker, Karina; Kutlu, Yalcin (Industrielle Beziehungen, 2020)
Der Artikel untersucht kollektives Interessenhandeln in der (Klein-)Kinderbetreuung in Deutschland und Österreich. Mit der Polanyi’schen Figur der Doppelbewegung werden die Dynamiken der aktuellen Aushandlungen im Feld der Sorge und Sorgearbeit aufeinander bezogen und analytisch gefasst. Die Bewegung in Form einer (Quasi-)Vermarktlichung steht im Spannungsverhältnis zum ausgeprägten Berufsethos der ErzieherInnen, um das sie durch Proteste (Österreich) und Streiks (Deutschland) kämpfen.
Keywords: (Early) Child care; (Klein-)Kinderbetreuung; (Quasi-)Vermarktlichung; (quasi) marketization; D63; Industrial Relations. JEL: B54; Industrielle Beziehungen; J81; Polanyi; Sorgearbeit; care work